- #1

- 9

- 0

## Main Question or Discussion Point

Use laplace Transform to solve this ode:

So I got:

sV(s)-V(0)-12V(s)=U(s+5)

V(s)(s-12)=U(s+5)+1

V(s)=[U(s+5)+1]/(s-12)

Now to go back to time domain with Inverse Laplace Transform...My question is, how to transform U(s+5)/(s-12)?

Any help?

Thanks guys

So I got:

sV(s)-V(0)-12V(s)=U(s+5)

V(s)(s-12)=U(s+5)+1

V(s)=[U(s+5)+1]/(s-12)

Now to go back to time domain with Inverse Laplace Transform...My question is, how to transform U(s+5)/(s-12)?

Any help?

Thanks guys